Volume 5A: Heat Transfer 2014
DOI: 10.1115/gt2014-25818
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Applicability of Transporting Water Mist for Cooling Turbine Blades

Abstract: This paper presents a numerical study to investigate the feasibility of transporting water mist to the rotating blades of a high pressure turbine. The idea of using mist film cooling to enhance conventional air cooling has been proven to be a feasible technique under laboratory conditions. However, there are challenges in implementing this scheme for real gas turbine systems. The first challenge is how to transport the mist to the rotating blades and the second challenge is delivering the mist to the injection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…It is found that different coolants have insignificant influence on morphology and distribution of secondary flows. Meanwhile, the velocity contour plots I did not see the plots of these secondary flows suggest that the velocity in mist/steam cooling and mist/air cooling ribbed channel is slightly lower than that in corresponding steam cooling and air cooling channel, due to the entrainment effect of water droplets when the water droplets are suspended in the flow and transported by steam and air flow via drag [18]. However, the decrease of velocity in mist/steam and mist/air cooling channel is minimal due to a small mist mass ratio (only 2% mist) in this study.…”
Section: Secondary Flow Distribution and Its Eeffect On Heat Transfermentioning
confidence: 97%
See 1 more Smart Citation
“…It is found that different coolants have insignificant influence on morphology and distribution of secondary flows. Meanwhile, the velocity contour plots I did not see the plots of these secondary flows suggest that the velocity in mist/steam cooling and mist/air cooling ribbed channel is slightly lower than that in corresponding steam cooling and air cooling channel, due to the entrainment effect of water droplets when the water droplets are suspended in the flow and transported by steam and air flow via drag [18]. However, the decrease of velocity in mist/steam and mist/air cooling channel is minimal due to a small mist mass ratio (only 2% mist) in this study.…”
Section: Secondary Flow Distribution and Its Eeffect On Heat Transfermentioning
confidence: 97%
“…Theoretically, it is encouraging for applying mist cooling to both gas turbine vane and blade under elevated operating conditions; and the performance of mist cooling has been moderately investigated. Wang et al [17,18] explored explore the feasibility of applying mist cooling to gas turbine vanes and blades by numerical simulation method. The results demonstrated that theoretically, it was encouraging for applying mist cooling to both gas turbine vane and blade under elevated operating conditions.…”
Section: Introductionmentioning
confidence: 99%